2004
DOI: 10.1177/1045389x04039262
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Shape Control of Distributed Reflectors with Discrete Piezoelectric Actuators

Abstract: In the current article, a novel approach to the shape control problem with a limited number of discrete actuators is presented. In optimizing the actuator locations, first the reference input was expanded with a representative set of eigenfunctions. From the expansion coefficients, the dominant modes in the reference input were identified. Next the distributed parameter system was rewritten in modal coordinates and the irrelevant modes were truncated. Finally, the actuator locations were selected such that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…They found that the beam shaping increases the coverage area by 40% while a beam-steering scanning angle of 10°is achieved. Andoh et al (2004) investigated the problem of shape control in the antenna reflector with a minimum number of actuators. Locations of the actuators were optimized by removing the unnecessary modes from the modal coordinates.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the beam shaping increases the coverage area by 40% while a beam-steering scanning angle of 10°is achieved. Andoh et al (2004) investigated the problem of shape control in the antenna reflector with a minimum number of actuators. Locations of the actuators were optimized by removing the unnecessary modes from the modal coordinates.…”
Section: Introductionmentioning
confidence: 99%
“…Background and Research Goal I N many adaptive structural system concepts, large numbers of actuators are utilized to achieve high authority and near distributed control actions. Many studies to date (Andoh et al, 2004;DeSmidt et al, 2006;Chen et al, 1991) have assumed that each actuator can be controlled individually. While ideally each actuator should be controlled by an individual power supply, at times it is not realistically feasible due to design, weight, or cost constraints.…”
Section: Introductionmentioning
confidence: 99%
“…In [10,16], finite element models for simply supported rectangular PVDF laminates are studied. Control algorithms based on analytical and numerical laminate models are discussed in [2,3,13].…”
Section: Introductionmentioning
confidence: 99%